2011
DOI: 10.1002/cmdc.201100426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Platinum–Ethacrynic Acid Conjugates in the Treatment of Mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) cells are characterized by chemoresistance associated with glutathione (GSH) metabolism. Ethacrynic acid (EA) is able to inhibit the detoxifying enzyme glutathione-S-transferase (GST), which catalyzes the conjugation between GSH and Pt-based drugs. With the aim of obtaining active bifunctional drugs, a Pt(II) complex containing two EA moieties as leaving groups, namely cis-diamminobis(ethacrynato)platinum(II), was synthesized, characterized, and tested on four MPM cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…As a term of comparison, the cis-diamminobis(ethacrynato)platinum(II) complex with the two EA moieties acting as leaving groups (Figure 4, complex XIII) was also synthesized and tested together with the Pt(IV) analogue on different primary MPM cancer cell lines. 44 Both complexes resulted more active than carboplatin with the platinum(IV) dual compound more potent in all cases with better resistance factors although less cytotoxic than cisplatin. In a similar manner the axial positions could be occupied by different pharmacophores that in principle could offer the possibility to act on different targets in a synergistic way.…”
Section: Mpm New Platinum Drugs In Vitro Evaluationmentioning
confidence: 98%
“…As a term of comparison, the cis-diamminobis(ethacrynato)platinum(II) complex with the two EA moieties acting as leaving groups (Figure 4, complex XIII) was also synthesized and tested together with the Pt(IV) analogue on different primary MPM cancer cell lines. 44 Both complexes resulted more active than carboplatin with the platinum(IV) dual compound more potent in all cases with better resistance factors although less cytotoxic than cisplatin. In a similar manner the axial positions could be occupied by different pharmacophores that in principle could offer the possibility to act on different targets in a synergistic way.…”
Section: Mpm New Platinum Drugs In Vitro Evaluationmentioning
confidence: 98%
“…The activation of the inhibitor by its target enzyme and covalent binding accounts for the strong and irreversible inhibition of enzymatic activity by the platinum complex. Interestingly, Zanellato et al [ 93 ] found that Pt(IV and II)-ethacrynic acid conjugates showed poorer performance than the reference drug cisplatin alone or in combination with EA did in the treatment of MPM, and cellular GST activity remained consistently unchanged. This may be related to the type of cancer.…”
Section: Bifunctional Pt(iv) Prodrugsmentioning
confidence: 99%
“…Combining CYP51 inhibition characteristics with bioreduction properties of a nitro-group in one molecule may offer a better solution in drug development against Chagas disease and other trypanosomatid-induced diseases. This strategy has been successfully used in numerous occasions, including drugs for cancer, asthma and chronic obstructive pulmonary disease as well as neurodegenerative diseases [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%